2018
DOI: 10.1111/aos.13932
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oximetry and systemic arterial oxygen levels

Abstract: Acta Ophthalmologica 2018 100% s urefnis: Inn€ ondun 100% s urefnis j ok s urefnismettun slagaeðlinga ı 94.5 AE 3.8% til samanburðar við 92.0 AE 3.7% aður en h un h ofst (n = 30, p < 0.0001). I bl aaeðlingum j okst s urefnismettunin ı 76.2 AE 8.0% fr a 51.3 AE 5.6% (p < 0.0001) aður en inn€ ondunin h ofst. Mismunur s urefnismettunar ı slag-og bl aaeðlingum laekkaði marktaekt a meðan a inn€ ondun s urefnisins st oð (18.3 AE 9.0% versus 40.7 AE 5.7% aður, p < 0.0001). Sj onhimnus urefnismaelingar ı alvarlegri la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 218 publications
(328 reference statements)
0
19
0
Order By: Relevance
“…We hypothesize that local factors may play a crucial role when it comes to the retinal vascular regulation and responses in metabolic diseases. In fact, a recent thesis (Eliasdottir, 2018) has suggested that retinal autoregulation is mostly due to myogenic and metabolic factors in order to accommodate local blood flow to differences in perfusion pressure and metabolic needs. In this context, we think that this protocol, once established, could be used to assess functional changes in the retinal vascular physiology before clinically detectable diseases, taking the paradigmatic example of DR.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that local factors may play a crucial role when it comes to the retinal vascular regulation and responses in metabolic diseases. In fact, a recent thesis (Eliasdottir, 2018) has suggested that retinal autoregulation is mostly due to myogenic and metabolic factors in order to accommodate local blood flow to differences in perfusion pressure and metabolic needs. In this context, we think that this protocol, once established, could be used to assess functional changes in the retinal vascular physiology before clinically detectable diseases, taking the paradigmatic example of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal vessels, the only vessels that can be observed directly in vivo, are ideal windows for evaluating the state of carotid atherosclerosis (Torres et al 2013). The blood perfusion of the ophthalmic artery, the first branch of the internal carotid artery (Eliasdottir 2018), is directly affected by the internal carotid artery (Kawaguchi et al 2006). Carotid artery stenosis and plaques are closely related to retinal artery occlusion (Miyazawa et al 2011) and retinal venous occlusion (Matsushima et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from Eliasdottir. 121 © 2018 Acta Ophthalmologica Scandinavica Foundation. Published by John Wiley & Sons Ltd, based on data from Zijlstra et al 122…”
Section: Current Productsmentioning
confidence: 99%